Prioritization by Multicriteria: balanced-tree methodology - da Silva, José Carlos (2022)
Choosing an appropriate methodology is essential to generate reliable prioritizations in support of a decision-making process. The prioritization of projects, for example, is one of the main activities to support the decision-making of managers, helping to justify the selection, cutting and allocation of resources among the projects in a portfolio. This article aims to present a new prioritization methodology for multicriteria decisions based on the combination of Miller's Law and Pareto's Principle. As the main intended contribution, there is the expectation of being able to carry out multicriteria prioritizations with less effort, particularly when many prioritized elements are involved, with the certainty of achieving adequately consistent and reliable results.